A special section on novel technologies and scientific advances in translational cardiovascular and neurological research - Wong, Kelvin K. L. (2019)
Breakthroughs in technologies have helped us to advance the understanding of the heart and brain, from cell to organ level. At the same time, the computing hardware and software continue to grow exponentially over the last decade. This gives a great opportunity for researchers and clinicians to utilize the growing computing power to better understand cardiovascular and neurological disease and integrate different information into clinical diagnosis and patient management. In order to decode these data in the form of an in-depth understanding of the fundamental behaviours of the heart and brain, to discover the mechanisms and progression of cardiovascular and neurological disease patterns, and to establish the foundation for clinical care and management of these diseases, a large number of researchers and clinicians started to utilize the growing computing power to explore the unknown dimensions of cardiovascular and neurological system. These new understanding and finding not only can broaden the definition of cardiology and neurology, but also possibly might reshape the whole medicine.